FAKTOR EKSTERNAL YANG MEMENGARUHI KEPUASAN KERJA PERAWAT - Syifa Aulia; Heri Ridwan; Iyos Sutresna (Jurnal Keperawatan Malang, 2024)
Background: Health care is provided to the whole of the community without exception, including convicts. However, there are numerous issues beyond individual control, such as overcrowding of inmates exceeding penitentiary capacity and issues regarding healthcare such as insufficient healthcare staff and nurses having to be on call outside of their regular duty hours, be the factor that affect nurse’s job satisfaction at Class IIB Sumedang Penitentiary Purpose: To determine the external factors affecting nurse job satisfaction at the Class IIB Sumedang Penitentiary. Methods: This research used a qualitative method with a descriptive case study. Data collection techniques include interviews, observations, and documentation. The data is then analyzed using the Miles and Huberman model, which consists of three stages: data reduction, data display, and conclusion drawing. Triangulation technique is also used for validity of the data through interviews with two nurses at the Class IIB Sumedang Penitentiary, observations conducted by the researcher, and documentation. Result: The result showed that external factors affecting nurse job satisfaction at the Class IIB Sumedang Penitentiary include nurse workload, nurse motivation, work environment and relationships with colleagues, as well as remuneration. Implication: The institution is advised to increase the number of healthcare staff, in line with the ideal ratio between healthcare workers and the number of inmates, and to appoint a permanent doctor to serve in the penitentiary clinic to provide optimal treatment to the inmates. Improving healthcare facilities to meet clinic standards is also recommended.